Iran’s Asymmetric Interventionism: The Analysis of the Proxy Warfare Strategy Since 2011 - Kanan, Ahmadzada (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2024)
The aim of this article is to examine and evaluate Iran’s indirect military intervention through the utilization of local non-state actors in the conflict zones of the Middle East. Particular attention was paid to the gray zone confrontation between Iran and the U.S.-led alliance after the outbreak of the Arab Spring in 2011. What are the characteristics of Iran’s proxy warfare (PW) dynamics, and to what extent has this strategy been effective in attaining its objectives? In this regard, PW theory has been chosen as the main theoretical framework, with its most recent advances in the literature. The paper argues that Iran’s adoption of PW strategy ultimately aims a) to reduce perceived threats originating from the U.S.-led alliance, b) deter potential military interventions on its soil, and c) render the U.S. presence in the Middle East burdensome with the ultimate aim of its withdrawal from the region over the long term. Moreover, it contends that although it comes at a cost and poses significant risks for Tehran, this strategy demonstrated effectiveness within the context of Iran’s prioritized principles. A primary contributing factor to Iran’s effective implementation of this strategy lies in its partnership style with its clients. Indeed, besides their strategic objectives, the main factor ensuring the resilience of the proxy alliance is the ideological affinity between the Iranian regime and the client forces. Celem artykułu jest zbadanie i ocena pośredniej interwencji wojskowej Iranu poprzez wykorzystanie lokalnych aktorów niepaństwowych w strefach konfliktu na Bliskim Wschodzie. Szczególną uwagę zwrócono na konfrontację w szarej strefie między Iranem a sojuszem pod przywództwem USA po wybuchu Arabskiej Wiosny w 2011 r. Jakie są cechy dynamiki irańskiej wojny zastępczej (WZ) i w jakim stopniu strategia ta była skuteczna w osiągnięciu swoich celów? W związku z tym jako główne ramy teoretyczne wybrano teorię WZ, wraz z jej najnowszymi osiągnięciami w literaturze. W artykule argumentuje się, że przyjęcie przez Iran strategii WZ ostatecznie ma na celu: a) ograniczenie dostrzeganych zagrożeń pochodzących ze strony sojuszu pod przywództwem USA; b) powstrzymanie potencjalnych interwencji wojskowych na jego terytorium oraz c) uczynienie obecności USA na Bliskim Wschodzie uciążliwą; c) uczynić obecność USA na Bliskim Wschodzie uciążliwą, mając na celu ostateczne wycofanie się z regionu w perspektywie długoterminowej. Ponadto utrzymuje, że chociaż wiąże się to z kosztami i stwarza znaczne ryzyko dla Teheranu, strategia ta wykazała skuteczność w kontekście priorytetowych zasad Iranu. Głównym czynnikiem przyczyniającym się do skutecznej realizacji tej strategii przez Iran jest partnerski styl Iranu wobec klientów. W rzeczywistości oprócz celów strategicznych głównym czynnikiem zapewniającym odporność sojuszu zastępczego jest pokrewieństwo ideologiczne między reżimem irańskim a siłami klienta.
Asymetryczny interwencjonizm Iranu: analiza dynamiki wojny proxy od 2011 roku
Keywords: Iran; proxy war; Middle East; Axis of Resistance; military strategy; wojna zastępcza; Bliski Wschód; Oś Oporu; strategia militarna